2012
DOI: 10.1016/j.jpainsymman.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Muscle Contractile Property Changes at the Time of Perceived Physical Exhaustion Suggests Central Mechanisms Contributing to Early Motor Task Failure in Patients With Cancer-Related Fatigue

Abstract: CRF patients perceive physical exhaustion sooner during a motor fatigue task with minimal muscular fatigue. The observation supports that central fatigue is a more significant factor than peripheral fatigue in causing fatigue feelings and limits motor function in cancer survivors with fatigue symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…In the same way, the curvature constant (τ) of the force-time relationship and the force variability (RMSSD) were not statistically different between both groups (Table 1). Similar force variability has previously been observed between CRF patients and a control group [33] indicating that this mechanical parameter does not allow discriminating the neuromuscular function of individuals suffering from cancer to healthy ones.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the same way, the curvature constant (τ) of the force-time relationship and the force variability (RMSSD) were not statistically different between both groups (Table 1). Similar force variability has previously been observed between CRF patients and a control group [33] indicating that this mechanical parameter does not allow discriminating the neuromuscular function of individuals suffering from cancer to healthy ones.…”
Section: Discussionsupporting
confidence: 65%
“…Since the deteriorated resistance to acute exercise may partly explain the fatigue subjectively felt in cancer populations [31], several experiments recently focused on fatigability alterations in fatigued cancer survivors. Some studies reported that during sustained [32][33][34] or intermittent [35] submaximal isometric contraction of the elbow flexors until volitional task failure, cancer survivors stopped sooner in comparison to age-and sex-matched healthy controls. However, other studies did not evidence different maximal voluntary force decrease [36,37] nor endurance time [36] after sustained contractions between fatigued and non-fatigued cancer survivor [37] or control participants [36].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in surface EMG activity may reflect changes in motor unit recruitment strategy by the CNS (the increase of motor unit synchronization) and/or peripheral changes, such as impairments in neuromuscular transmission or action potential propagation along the muscle fibers. Our findings of smaller increases in EMG amplitude and substantial twitch interpolated force near exhaustion in CRF suggest reduced ability of the central nervous system to recruit motor units to maintain the contraction, which resulted in earlier task failure and a lower level of muscle fatigue indicated by insignificant changes in muscle contractile properties [8] and lower myoelectrical manifestation of fatigue in the CRF patients. Greater central fatigue has previously been observed in aging [19], [30], multiple sclerosis [31], and chronic fatigue syndrome [32].…”
Section: Discussionmentioning
confidence: 72%
“…In addition, other parameters derived from the twitch force can show alterations in contractile properties of the muscle such as fatigue-induced slowing the rate of muscle contraction and relaxation [7]. A lack of fatigue-related muscle contractile property changes at the time of perceived physical exhaustion has recently been reported in cancer survivors with fatigue symptoms [8]. A recent study examined as well electrical stimulation-evoked muscle force during voluntarily generated sustained force from the biceps brachii [9].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the patients with fatigue failed earlier in motor tasks, but that this is not associated with changes in contractile properties. This lack of contractile impairment implicates a central activation failure [18].…”
Section: Physical Fatiguementioning
confidence: 95%